(untitled) (The Proceedings of The International Conference on Climate Change, 2018)
Climate change is possibly one of the most urgent and complex issue being faced by nations worldwide. Rising levels of greenhouse gas emissions is considered by scientists and academics to be the primary cause for increasing temperatures, which is known to result in global warming and cause climatic changes. Therefore, adopting measures and strategies to mitigate the adverse impacts being caused due to rising emissions is high on the agenda for policy makers and governments across the globe. Many sectors are responsible for feeding this rise in GHG emissions, including transport. In India, transport is the second largest greenhouse gas emitter from the energy sector. Despite the fact that a majority of GHG emissions in the Indian transport sector is from roadways, and rail transport is only responsible for 5% of the total transport emissions, the exponential increase in rail emissions over the past few years makes it imperative to focus on strategies and technologies to reduce the same. While current research is being undertaken to increase the share of railways due to their carbon friendly nature in comparison to road transport, it is submitted that a deeper engagement with developing and using actual low-carbon alternatives is required, which can in-reality help in achieving reduced emissions, and consequently bring down the GHG emissions from rail transport in India. Low-carbon alternatives, such as use of clean fuels and electrification of the rail network, are now being developed with the aim to move from using carbon intensive sources of energy to environment friendly ones. This paper discusses these GHG emissions reduction strategies being implemented by the Indian government within the rail network to determine whether these are in-reality assisting or have the potential to assist in bringing down the GHG emissions from railways in India. This will also determine the scope of climate change mitigation from these low-carbon alternatives being adopted by the government in the Indian rail transport sector.